8th AIAA Flow Control Conference 2016
DOI: 10.2514/6.2016-3257
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the filtering effect of the stochastic estimation and accuracy improvement by sensor location optimization

Abstract: The reconstruction of the flow behind a backward facing step at a Reynolds number of 60,000 using Linear Stochastic Estimation (LSE) and modified is investigated. In particular, the turbulent spatial integral length scales reconstructed for several sensor configurations are studied. The reconstruction of the Proper Orthogonal Decomposition (POD) modes is also performed in order to show the limitations of the LSE reconstruction for complex flows, for which taking into account only a few POD modes is not enough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Sensor locations are chosen at random as literature discussed suggests that sensor location can impact the accuracy of resulting estimations. The purpose of this work is not to optimise sensor location selection (for that, see Arnault et al 22 and Cohen et al 24 ) but instead to provide a guide for the number of sensors required for an acceptable accuracy of estimation. Therefore, locations are randomised and the investigation is repeated a total of 10 times, and the mean is taken to exclude the effects of sensor location.…”
Section: Estimation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Sensor locations are chosen at random as literature discussed suggests that sensor location can impact the accuracy of resulting estimations. The purpose of this work is not to optimise sensor location selection (for that, see Arnault et al 22 and Cohen et al 24 ) but instead to provide a guide for the number of sensors required for an acceptable accuracy of estimation. Therefore, locations are randomised and the investigation is repeated a total of 10 times, and the mean is taken to exclude the effects of sensor location.…”
Section: Estimation Methodologymentioning
confidence: 99%
“…In a large number of studies, sensors used in the LSE technique have been in the form of wall pressure sensors 3,4,10,21 or microphone-based sensors 9 as these quantities are often less intrusive to measure. Arnault et al 22 describe the limitations in estimating smaller scales of turbulence using wall-based pressure measurements. However, the study goes on to demonstrate that improvements may be made by considering sensor location optimisation according to an algorithm developed by Muradore et al 23 Arnault et al 22 found improvement when the sensor locations were close to the extrema of POD modes which agrees with work by Cohen et al 24…”
Section: Introductionmentioning
confidence: 99%
“…al. [29] who show the limitations in the estimation of smaller turbulent structures which may not correlate well with these measurements. The study does however progress to show that it is possible to optimize the sensor locations to improve correlation using an algorithm developed by Muradore et.…”
Section: Linear Stochastic Estimationmentioning
confidence: 99%